DIGITAL CONTENT AND THE IMPACT OF VERBAL COMMONALITY ON DIFFERENT JURISPRUDENTIAL RULINGS - AN APPLIED STUDY - Yousef A. Baker, El-Ebiary; Walid Mohamed, Abdelrahman Mohamed; Mohamed Rady, Mohamed Elpaz Elsheakh; Muhamad Zhafri, Mohammad Nazmi (2020)
This study aimed to find out the impact of Islamic digital content on the Internet. Knowledge is considered the basic issue and intellectual ideology of societies that aspire to develop to become in the ranks of scientifically and cognitively advanced societies as knowledge and modern technology are complementary to each other and each of them is considered an entrance and a measure of the development of societies in our present time. The research also aims to clarify the meaning of the verbal joint, the comparison between its reality according to both linguists and fundamentalists, explain its reasons, and its relationship to some fundamentalist terms, and study some of the verbal joint words, which have a juristic effect, and the research includes some applied models for the verbal joint that have a juristic effect, And clarifying the way to participate in it, and mentioning the jurisprudential issues resulting from this participation, and I followed in this research the comparative analytical inductive approach, which is based on tracking what is related to the verbal participant in the books of linguists and fundamentalists as well as jurists, and analyzing and comparing it with others, while tracing the jurisprudential implications that resulted from it. Among the most important findings of the research: that the verbal commonality is a sign of the development of the Arabic language, and it is permissible to ever occur in speech in the Qur’an and the Sunnah, and others. Because usage is evidence of participation, and whether the verbal participant is less or more, and because of its presence in some of the legal texts, because of it the difference between the jurists has occurred. The research reached important results that are listed.